Vamos, aprendamos sobre el movimiento de los cuerpos - Quezada Rojas, Magna Eufemia (2020)
We are surrounding of things that constantly move in our daily life. It is sometimes easy to observe how a car gets moving in the street, the turn of the wheels, the flight of the birds, people walking, etc. However, sometimes it is not that easy to observe some movements for example, a glass of water which apparently is still on the ground. But if we analyse that the Earth moves around itself and around the Sun then the glass of water moves as well._x000D_ Kinematics is the part of Physics which studies the movement of bodies without taking into account the cause that produces it. The aim of this work is to talk about the movement of bodies and the identification of each one of the elements in it. This will allow us to calculate and solve problematic situations in our environment such us the speed of a mobile, the time a vehicle might take to cover a specific distance, among others.